Responsiveness of a simple RAPID-3-like index compared to disease-specific BASDAI and ASDAS indices in patients with axial spondyloarthritis - Castrejón, Isabel (RMD Open, 2016)
OBJECTIVE: To evaluate the responsiveness of a simple routine assessment of patient index data (RAPID3)-like index that includes only 3 patient self-report measures (physical function, pain and patient global estimate) compared to that of traditional composite indices to assess change in patients with axial spondyloarthritis (Ax-SpA). METHODS: Devenir des Spondylarthropathies Indifférenciées Récentes (DESIR) is a prospective cohort of patients with inflammatory back pain suggestive of Ax-SpA. The study included 461 patients, who met the Assessment of SpondyloArthritis International Society (ASAS) classification criteria for Ax-SpA. A simple RAPID3-like index was compared with the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the AS Disease Activity Score (ASDAS) scores for responsiveness over 6 months. Construct validity was also evaluated through Pearson correlations and discrimination of disease activity through standardised mean differences for the 3 indices. RESULTS: The RAPID3-like index was correlated significantly with BASDAI (r=0.84, p<0.005) and ASDAS-C-reactive protein (CRP) (r=0.74, p<0.005), similar to correlations of BASDAI with ASDAS-CRP (r=0.76, p<0.005). The percentage of patients with inactive disease ranged from 9% to 25% and with high activity from 10% to 45%, according to various measures. The capacity to discriminate between high and low disease activity was similar for the 3 indices. The strength of agreement of RAPID3 with ASDAS-CRP was moderate (0.44) and lower with BASDAI (0.37). Responsiveness over 6 months was slightly higher for ASDAS-CRP and the RAPID3-like index than that for BASDAI. CONCLUSIONS: The RAPID3-like index provides similar information to BASDAI and ASDAS-CRP concerning responsiveness over 6 months. RAPID3 appears feasible to assess patients with Ax-SpA quantitatively over time in busy clinical settings.